[Gdańsk Orunia, ul. Brzegi] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia Kanał Raduni i fragment ul. Brzegi. Widok od. ul. Podmiejskiej w kierunku kościoła św. Ignacego, ok. 1910 r.